Analysis of global patents on potato processing with special reference to Chinese experiences and Indian outlook: implications for future potato processing industry - Rana, Rajesh K.; Martolia, Renu; Singh, Vikram (Potato Journal, 2017)
Potato has been considered as a serious food security option worldwide and about 15.5% of potato tubers are processed into various products. This study undertakes analysis of patents data for having insight into the direction and extent of global research on potato processing. North America has demonstrated that protection of intellectual properties create global businesses, however massive efforts from China in recent years indicate their gigantic future plans in potato processing. The study indicates that western developed world was skewed towards French fries and Potato Chips/ Crisps while China has greater balance in their focus as Other Potato products, Dehydrated Products and Processing Machinery have also been adequately focussed.